2009
DOI: 10.1007/s12149-008-0209-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrated FDG-PET/CT compared with intravenous contrast-enhanced CT for evaluation of metastatic regional lymph nodes in patients with resectable early stage esophageal cancer

Abstract: Integrated PET/CT improves the PPV of regional LNs when compared with CECT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 21 publications
3
27
1
1
Order By: Relevance
“…This value is higher than the previously reported mean SUVmax of metastatic LNs of esophageal SCC (25). We suspected that the higher prevalence of reactive inflammatory LNs in the thoracic field elevated the optimal cutoff criterion to separate the malignant versus inflammatory pathologies.…”
Section: Discussioncontrasting
confidence: 56%
“…This value is higher than the previously reported mean SUVmax of metastatic LNs of esophageal SCC (25). We suspected that the higher prevalence of reactive inflammatory LNs in the thoracic field elevated the optimal cutoff criterion to separate the malignant versus inflammatory pathologies.…”
Section: Discussioncontrasting
confidence: 56%
“…The recent use of PET/CT imaging with co-registration of anatomical and functional imaging data has improved the localisation of regions of increased FDG uptake and the accuracy of staging in patients with oesophageal cancer [15,16]. Okada et al [16] found that the sensitivity, specificity and accuracy of PET/CT for detecting metastatic regional lymph nodes were better than those of CT (60 vs 56%, 99.5 vs 97.3% and 94.8 vs 92.4%, respectively). In our study, however, PET/CT showed worse specificity and accuracy for detecting metastatic regional lymph nodes in patients with oesophageal cancer when compared with CT, despite a similar sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…et al compared the enlargement of lymph node based on CT scanning with that diagnosed by pathological examination in 41 cases of esophageal cancers, proposing 5 mm as the diagnostic criteria of short diameter, the sensitivity and specificity of which were 68% and 87%, respectively (Mizowaki et al, 1996). Currently most investigators take 10 mm as the lower limit of lymph node metastasis, with the sensitivity and specificity of which are 11%~77% and 71%~97.3%, respectively (Yoon et al, 2003;Okada et al, 2009;Ma et al, 2013). The enhanced features of metastatic lymph nodes from different pathology of primary tumors showed different under MSCT scanning, usually displaying as ring-shaped and thin-wall enhancement.…”
Section: Discussionmentioning
confidence: 99%